2021
DOI: 10.1098/rspb.2020.2192
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and genetics of sexually dimorphic ‘dual’ mimicry in the butterflyElymnias hypermnestra

Abstract: Sexual dimorphism is a major component of morphological variation across the tree of life, but the mechanisms underlying phenotypic differences between sexes of a single species are poorly understood. We examined the population genomics and biogeography of the common palmfly Elymnias hypermnestra , a dual mimic in which female wing colour patterns are either dark brown (melanic) or bright orange, mimicking toxic Euploea and Danaus species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…To address the biology of WntA, one must first identify a system where WntA functions can be distinguished from other Wnts, and the butterfly wing system is ideal for this endeavor due to its two‐dimensionality. Genetic and developmental studies of the family Nymphalidae have shown first, that WntA regulatory alleles drive adaptive pattern shape variation across populations of Heliconius, Limenitis and Elymnias butterflies (Gallant et al, 2014; Huber et al, 2015; Martin et al, 2012; Martin & Courtier‐Orgogozo, 2017; Moest et al, 2020; Morris et al, 2019; Ruttenberg et al, 2021; Van Belleghem et al, 2017); second, that WntA expression in larval wing imaginal disks varies widely between species, but always prefigures the position of many color pattern elements of the Nymphalid Ground Plan (Martin & Reed, 2014; Mazo‐Vargas et al, 2017; Schwanwitsch, 1956); and finally, that WntA is necessary for pattern induction and for the formation of color domain boundaries in all nymphalid species studied so far, as shown in clustered regularly interspaced short palindromic repeats (CRISPR) mosaic knockout (mKO) experiments (Concha et al, 2019; Mazo‐Vargas et al, 2017). WntA is thus a key determinant of color pattern formation and diversification in butterfly wings, with both conserved and derived functions, but its molecular mode of action requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…To address the biology of WntA, one must first identify a system where WntA functions can be distinguished from other Wnts, and the butterfly wing system is ideal for this endeavor due to its two‐dimensionality. Genetic and developmental studies of the family Nymphalidae have shown first, that WntA regulatory alleles drive adaptive pattern shape variation across populations of Heliconius, Limenitis and Elymnias butterflies (Gallant et al, 2014; Huber et al, 2015; Martin et al, 2012; Martin & Courtier‐Orgogozo, 2017; Moest et al, 2020; Morris et al, 2019; Ruttenberg et al, 2021; Van Belleghem et al, 2017); second, that WntA expression in larval wing imaginal disks varies widely between species, but always prefigures the position of many color pattern elements of the Nymphalid Ground Plan (Martin & Reed, 2014; Mazo‐Vargas et al, 2017; Schwanwitsch, 1956); and finally, that WntA is necessary for pattern induction and for the formation of color domain boundaries in all nymphalid species studied so far, as shown in clustered regularly interspaced short palindromic repeats (CRISPR) mosaic knockout (mKO) experiments (Concha et al, 2019; Mazo‐Vargas et al, 2017). WntA is thus a key determinant of color pattern formation and diversification in butterfly wings, with both conserved and derived functions, but its molecular mode of action requires further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Sexually dimorphic color patterns of animals are also derived from mimetic evolution between the species with warning coloration. Theoretically, the following four types of mimicry evolution should occur: unimodal, female-limited, male-limited and dual mimicry (Vane-Wright 1971;Hespenheide 1975;Kunte 2009;Allen et al 2011;Ruxton et al 2018). In the unimodal mimicry, both sexes resemble the same poisonous or unpalatable model species, and therefore, sexual dimorphism in color does not occur.…”
Section: Introductionmentioning
confidence: 99%
“…Dual mimicry, in which each sex resembles a different model species, causes a great difference in color between the sexes. Among the latter three types causing sexually dimorphic coloration, female-limited mimicry has been studied since 1865 when Wallace (1865) recorded seven examples of female-limited mimicking butterflies (Ruxton et al 2018). However, only a few examples are recorded so far for male-limited mimicry (Reiskind & Levi 1967;Vane-Wright 1974;Hespenheide 1975;Waldbauer & Sternburg 1975, 1987Sternburg et al 1977;Jeffords et al 1979Jeffords et al , 1980Gilbert 2005) and dual mimicry (Evans 1968(Evans , 1969Vane-Wright 1971Heal 1981;Takiya et al 1999;Kunte 2008Kunte , 2009Wei et al 2017;Morinaka et al 2018;Panettieri et al 2018;Ruttenberg et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations